Self-healing fiber-reinforced composite metallic material utilizing melting–solidification and capillary action - Shota Miyake; Shunsuke Nagahama; Shigeki Sugano (Journal of Materials Research and Technology)
By imparting self-healing capabilities to metallic materials, various benefits such as extending system lifespan and reducing maintenance frequency can be achieved. However, in solid metals, the atomic mobility is inherently low and diffusion rates are limited, making intrinsic self-healing extremely challenging. In this study, we applied the melting-solidification phenomenon to enable atomic mobility and regenerate metallic bonds at crack sites. Additionally, we leveraged capillary action to maintain the shape of the liquid metal during self-healing, thereby enabling the development of a novel self-healing metallic material. The proposed material is a composite consisting of a low-melting-point (LMP) metal with self-healing properties and a braided wire structure composed of metallic strands that retain the LMP metal through capillary action. This composite not only exhibits self-healing capabilities but also features fiber reinforcement owing to its structural design, which addresses the inherent strength limitations of LMP metals. The performance of the proposed material was evaluated through experiments focusing on self-healing and fiber reinforcement. The results demonstrated that the material recovered up to 94.6 % of its maximum strength after self-healing. Furthermore, fiber reinforcement achieved a strength two-times greater than that of the LMP metal alone. These findings suggest that the proposed composite material effectively realizes the benefits of self-healing and enhanced mechanical strength, offering significant potential for practical applications in environments requiring robust and reliable materials.